First Case of Idiopathic Eosinophilic Meningoencephalitis in a Sheep. (January 2020) - Vidaña, B.; Floyd, T.; Brena, C.; Lyle, R.; Carson, A.; Hamilton, C.M.; Wessels, M.
Summary: A 1.5-year-old ewe was presented with neurological signs that had been observed from about 2 days prior to death. There had been no clinical response to anti-inflammatory and antibiotic treatment. Histopathological examination of the brain revealed a severe and widespread eosinophilic meningoencephalomyelitis of unknown aetiology. Defining histological features included diffuse angiocentric eosinophilic infiltrates in the neuroparenchyma and meninges, neuronal necrosis, astrocytosis, neuropil vacuolation and occasional glial scars. Differential diagnostics for eosinophilic meningoencephalitis were taken into account and investigated by means of special stains, immunohistochemistry, bacteriology and polymerase chain reaction. No pathological changes or ancillary tests were supportive or revealed a specific aetiology for the condition and therefore it was considered idiopathic. Idiopathic meningoencephalitis is a rare disease, mainly described in man and rarely in dogs, with no apparent aetiological cause or potential breed predisposition. To our knowledge this is the first case of idiopathic eosinophilic meningoencephalitis in a sheep and provides a histopathological guideline for prospective comparative pathology studies.